Revitalisasi pendidikan pancasila sebagai pondasi pembangunan karakter bangsa di era globalisasi - Agus, Andi Aco (Jurnal Ekonomi dan Riset Pembangunan, 2025)
In the context of national character building in Indonesia, it is reflected in the values ​​of Pancasila, namely: mutual cooperation, cooperation, mutual assistance and tolerance between ethnicities, religions, cultures, deliberation for consensus as a way of decision making. The spirit of unity and oneness, in diversity, social justice for all Indonesian people, the challenges in character education in the digital era are: the very fast and unfiltered flow of information, the influence of foreign cultures and globalization, and the lack of teacher skills in utilizing technology, lack of individualism and lack of direct social interaction, changes in learning patterns and various attention. Efforts to overcome the challenges are: strengthening digital literacy and value literacy, training and developing teacher competencies in the use of technology for learning Pancasila values, developing interesting and contextual digital learning media with Pancasila values, encouraging social interaction, and real activities that instill the values ​​of mutual cooperation, deliberation, tolerance, supervision and regulation of digital content so that negative content can be minimized. The strategy for revitalizing Pancasila education is an innovative and value-based approach, integration of technology and digital media, the role of educators, families and society, and government policies in revitalization.